Upper bound analysis of stability of dual circular tunnels subjected to surcharge loading in cohesive-frictional soils. (January 2017) - Yang, Feng; Zheng, Xiangcou; Zhang, Jian; Yang, Junsheng
Abstract: The stability of dual circular tunnels subjected to surcharge loading in cohesive-frictional soils, obeying the Mohr–Coulomb failure criterion, is determined by an upper bound finite element method combined with rigid translatory moving elements (UBFEM-RTME). The stability results, which are considered to be influenced by the soil internal friction angle ( ϕ ), ratio of the tunnel cover to the tunnel diameter ( C / D ), ratio of the tunnels' center-to-center distance to the tunnel diameter ( S / D ), and ratio of the product of the soil unit weight and the tunnel diameter to the soil cohesion ( γD / c ), are presented in the form of dimensionless stability numbers ( σs / c ) and failure mechanisms. The results reveal that the values of stability numbers decrease continuously with increasing γD / c and increase with increasing C / D, S / D, and ϕ, except in the cases of moderate depth and close proximity. Most of the obtained failure mechanisms are constituted by two wedge-shaped areas composed of two groups of crossed slip lines and a complete rigid area. The results of this study compare reasonably well with the solutions reported in the literature.